PENGARUH PROFITABILITAS, LEVERAGE DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG GO PUBLIC DI BURSA EFEK INDONESIA - Gildha Mita Amalia Gusti; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to analyze the effect of Profitability, Leverage, and Institutional Ownership on tax avoidance in food and beverage companies that go public on the Indonesian Stock Exchange. This type of research is quantitative, while according to the relationship between variables, this research is included in correlational research. This study uses the financial statements of food and beverage companies for 2017-2020. The data used is secondary data which is processed using SPSS software. The analytical method used is multiple linear regression. The study's results prove that (1) Profitability has a negative effect on Tax Avoidance on the Indonesia Stock Exchange (IDX). (2) Leverage has a positive effect on Tax Avoidance. (3) Institutional ownership has a negative effect on the Tax Avoidance of food and beverage companies on the Indonesia Stock Exchange (IDX)Keywords: Profitability, Leverage, Institutional  Ownership, Tax Avoidance